ETank and contemporary online tools for rainwater tank outcomes analysis. (2017) - Imteaz, Monzur A.; Karki, Ramesh; Shamseldin, Asaad; Matos, Cristina
This paper presents development of a comprehensive decision support tool (eTank) to analyse and optimise a rainwater tank size. The developed tool enables a simple quantitative analysis of the expected water that can be saved based on daily water balance concept. The tool produces graphs showing cumulative yearly rainwater used, overflow and augmented townwater supply. To account for climate variability, provision has been made in the tool to analyse for a particular option in three different climatic conditions (dry, average and wet). Also, the tool enables a life cycle costing and payback period analysis of any particular tank size through the simulated expected water savings per year, initial construction costs and operational. The outcomes of eTank are compared with other contemporary online tools in regards to rainwater savings. It is revealed that most of the tools overestimate the potential savings due to not considering several influencing factors.